El autobus magico en el museo encantado : un libro sobre los sonidos : from an episode of the animated TV series - Beech, Linda; Schick, Joel.; Cole, Joanna; Scholastic Productions (New York : Scholastic Inc., 1995)
The class is going to give a concert at the Sound Museum. On the way, the Magic School bus breaks down--in front of a big, old haunted house where the kids hear lots of weird noises. Ms. Frizzle and the kids enter at their own risk. But once inside they learn all about sound.
Translation of "The Magic School bus in the haunted museum."
Keywords: Sound; Music -- Acoustics and physics; Musical instruments; Spanish language materials